The “Digital Economy of the Russian Federation” national program as a support mechanism for the Russian information technology industry - E. N. Gavrilova (Вестник университета)
The current pace of information technology development of the economy has a significant impact on the social life. This explains the necessity of using a scientific approach to assess the effectiveness of the implementation of the “Digital Economy of the Russian Federation” national program as a tool of government regulation of the economy and determines the high relevance of the topic of the study. The goal of the article is to identify significant areas of regulation of the Russian information technology industry on the basis of the assessment carried out. The objective of the study was to perform comprehensive analysis of the economic situation of the Russian Federation using the example of the information technology industry and to propose measures aimed at addressing imbalances in the industry’s advancement. The author of the article examined performance indicators of the industry and provided a description of the national program under study. The econometric model constructed revealed a high level of influence that program implementation measures have on the competitiveness of the industry.